Water balance model for planning rehabilitation of a tank cascade irrigation system in Sri Lanka - Itakura, J. (International Irrigation Management Institute, 1995)
Since time immemorial, people in South Asia have collected rainfall runoff in small storage reservoirs (called tanks) for later use in agricultural production, for domestic use and watering of livestock. A unique feature of the tanks in Sri Lanka is that often several of the tanks are linked together through a canal. The resulting cascade of tanks should then be managed as one system. The Thirappane cascade, which is the topic of this study, falls within the catchment area of a much bigger reservoir, Nachchaduwa. The latter was built around 900 AD, and restored in 1906, when many of the tanks still in use now were surveyed and restored to use. Cascade management, however, was not always carried out properly and restoration work not done, that the skills to do so were lost. The management of these interconnected tanks presents many interesting questions, the answers to which hitherto have not been fully explored. The effectiveness of storage-based irrigation systems was such that over time more and more people were attracted to the command areas of the tanks and many of the systems became unsustainable due to overcrowding. The objective of this study was a limited one, i.e., to explore through simple water balance modelling several improved management options for a particular set of tanks in the Thirappane Cascade and to examine how the tank cascade can be stabilized through structural modifications. The water balance model developed for this purpose has deliberately been kept simple, requiring only data that can be easily collected in the field.